Analysis of trends of development of enterprise activity in the field of polymeric waste utilization in Ukraine - Lupinos, Anastasiia; Нurzhii Nataliia (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The purpose of the scientific article is to study the state of recycling PET bottles, the prospects for the development of the domestic market, taking into account the experience of foreign enterprises involved in the processing of plastic into a precious resource. Design/methodology/approach. In order to achieve this goal, the following tasks were solved: the tendencies of business development on plastic processing in the world and domestic practice were analyzed, the key players of plastic business in the territory of Ukraine were determined, and the prospects of the technology for processing PET bottles were described. Findings. The relevance of the work is the processes of urbanization significantly affect the deterioration of the environmental state of the environment, which in turn negatively affects the health of the nation. Accumulated waste in cities is disposed of in a timely manner and improperly, which results in their intensive accumulation. Unauthorized landfills are the main pollutant of surface and groundwater. As a result of entering into the reservoirs of chemicals released from waste, there is pollution of land and water sources. In recent times, many types of utilization are used, which allow to receive new raw materials for the production of finished products. The development of scientific technologies allows obtaining high-quality grades of fuel from waste plastic. The effect of such activity is energy saving. The transition to rational consumption of resources makes it possible to reduce the cost and specific capital investments, as a result of which the pace of economic growth is accelerating. One of the widespread recycling methods is the recycling of PET bottles from which polyester fiber is produced, which can return to us in the form of eco-clothing. Thus, when using the methods of recycling and recycling of plastic, the amount of garbage in the territory of Ukraine decreases. The object of the research is the state of the ecological environment of the regions of Ukraine, contaminated with waste. Research limitations/implications. The article analyzes the trends of entrepreneurial activity in the field of utilization of polymer waste in Ukraine. Possible ways of solving garbage collection problems are determined. Originality/value. The scientific significance of the work is to focus on the ecological problems of the contaminated regions of Ukraine and the practical application of ways to solve various methods of purification from the accumulation of polymer waste using them as a valuable resource.